INCREASING THE NURSING KNOWLEDGE CANVAS: EXAMINING ARTS-BASED RESEARCH AND TEACHING METHODS - Shagraa Hassan Ali Sufyani ‏Esam Rezgullah Megdad ‏Fatmah Jader Alshomrani ‏Hassan abdoh sawadi Layla Hassan Alqasmi ‏Sultan Mufareh Ahead Asiri,; Ahmed abdullah alhuwekan ‏Amna Abdullah AlMaqadi ‏Manar Mohammed alruwaili ‏Faimaa Mohammed alabsy ‏Abdulrahman Yahya Sahli Mohammed Ahmad Asseri ‏Ahlam Gharbi Alshammari ‏Fahad Abdu Shoei Humedi ‏Atif ogayby alkhayri,Sultan Mohammed AlShammari, (Chelonian Research Foundation, 2022)
The increasing use of arts-based research methodologies in nursing scholarship is examined in this work. It makes the case that these strategies add something worthwhile above and beyond conventional techniques by giving: Deeper and richer understandings:By integrating feelings and firsthand knowledge with factual data, art can help people grasp phenomena in a more comprehensive way. New channels of communication: Sharing research findings via creative forms can improve the retention of information and open up new channels of communication with audiences. Pedagogical instruments for fostering empathy and inquiry: In nursing education, arts-based approaches can be used to promote emotional intelligence, critical thinking, and a deeper comprehension of patient experiences. The overuse of Carper's (1978) paradigm to explain aesthetic knowing in nursing is criticized in this research. It offers an expanded viewpoint grounded on Dewey's aesthetics, emphasizing "knowing through" by actively participating in artistic creation and "knowing about" via the appreciation of art. The authors stress that more research is necessary to determine the exact processes via which arts-based techniques advance nursing knowledge. They demand continued discussion in order to create a solid theoretical framework for this nascent topic. Keywords: nursing education, empathy, communication in nursing, arts-based research, nursing knowledge, and aesthetic knowledge.